Pengaruh Pelatihan Kecerdasan Emosi terhadap Penurunan Agresivitas Anak di Sekolah - Herlina Sari; Irwan Nuryana Kurniawan (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2004)
The purpose of this research is to examine empirically whether emotional intelligence training was effective in reducing children aggression at school. This research used experimental method with treatments by subject design, which involved 50 elementary school pupils in Yogyakarta as study participants. This research used children aggression scale to reveal the degree of children aggression at school. The result of this research suggests that emotional intelligence significantly was effective in reducing children aggression at school. Practical and research future implication are discussed.Key Words : Emotional Intelligence Training, Children Aggression at School